An update on shellfish allergy. Issue 3 (June 2019) - Wong, Lydia; Tham, Elizabeth Huiwen; Lee, Bee Wah
Abstract : Purpose of review: Shellfish is an important cause of food allergy worldwide, and a major cause of food-triggered anaphylaxis. Despite the wide variety of shellfish, there is considerable serological and clinical cross-reactivity of major shellfish allergens, and accurate diagnosis remains a challenge in the management of shellfish allergy. Recent findings: Novel minor allergens have been discovered and characterized, and advances in component resolved diagnostics have provided insights into the prevalence of sensitization and their clinical importance in shellfish allergy. The extensive cross-reactivity between tropomyosin of house-dust mite and crustacean shellfish has been postulated to be the cause of a proposed mite-shellfish oral allergy syndrome. Summary: More studies in food challenge-proven patients are required to establish the true prevalence and natural history of shellfish allergy. Refinement of component resolved diagnostics and testing for minor allergens may be helpful in developing more precise species-specific tests. Further investigation into the role of tropomyosin in house-dust mite and shellfish allergies may provide novel immunotherapeutic approaches for shellfish allergy.